APPLICATION OF THE PIGMENT OF ACTINOBACTERIA ISOLATED FROM THE WASPS-NEST SOIL FOR DYEING SILK FIBERS - Urtgam , Sittichai; Thurnkul, Naruemol (Life Sciences and Environment Journal, 2021)
Actinobacteria-derived pigments are the emerging class of natural dyes, which have attracted significant attention for the development of novel natural pigments for fiber dyeing. This research aims to isolate actinobacteria from wasps-nest soil for dye production, silk fibers dyeing, examine the qualities of fibers dyed by pigments and identify actinobacteria species. The results showed that 10 isolates of actinobacteria could be isolated from wasps-nest soil using Sodium Caseinate Agar (SCA). Moreover, the obtained actinobacteria J10 exhibited the yellow color and show the best dyeing on silk fibers. To investigate the qualities of pigment, the textile characteristics of dyed silk fibers were analyzed with the color fastness to washing and light by following the standard methods namely ISO105-C06:2010(E) and ISO 105-B02:2014(E), respectively. The result showed that the fastness to washing was ranged in the 4 to 5 level, which referred to a very good acceptance level. However, the light fastness was observed in the 3 to 4 level, which referred to an intermediate acceptance. The identification of actinobacteria isolate J10 based on comparative sequence analysis of 16S rDNA gene revealed the similarity to Streptomyces costaricanus (99.57%), S. prasinopilosus (99.50%), S. rochei (99.50%), S. padanus (99.50%), and S. griseofuscus (99.50%). These actinobacteria were reported as Streptomyces spp. which could produce the secondary metabolites to apply for medical, agricultural and commercial purposes. Hence, the pigment could be potential candidates to further develop for textile dying applications.